Completeness and correctness of cerebral palsy diagnoses in two health registers: implications for estimating prevalence. (29th November 2016) - Hollung, Sandra Julsen; Vik, Torstein; Wiik, Robert; Bakken, Inger Johanne; Andersen, Guro L
Abstract : Aim: To assess completeness and correctness of cerebral palsy (CP) diagnoses in the Cerebral Palsy Register of Norway (CPRN) and the Norwegian Patient Register (NPR), and to estimate CP prevalence. Method: Among 747 883 Norwegian residents born from 1996 to 2007, 2231 had a diagnosis of CP in the NPR while 1441 were registered in the CPRN. Children registered in the CPRN were considered to have a valid CP diagnosis. For those with a diagnosis of CP only in the NPR, two paediatricians reviewed the hospital records. The prevalence rate of CP with 95% confidence intervals (CI) was calculated on the basis of the combined data sets. Results: One thousand three hundred and ninety‐eight children were registered with a diagnosis of CP in both registers, 43 children were only registered in the CPRN, and 824 only in the NPR. The review of hospital records revealed that 464 (59.5%) had CP. Thus, the NPR was 98% complete, and for 86% the diagnosis was correct. The completeness of the CPRN was 76%, while the diagnosis was considered correct for all children (100%). The resulting prevalence of CP was 2.5 (95% CI 2.4–2.7) per 1000. Interpretation: To gain accurate estimates of prevalence rates of CP, it is essential to combine data sources and to validate register data. What this paper adds: Administrative health registers are likely to overestimate the prevalence of cerebral palsy (CP). Medical quality consent‐based registers are likely to underestimate the prevalence of CP. Multiple sources and case review are needed for more accurate prevalence estimates. Prevalence of CP in Norway is 2.4 per 1000 live births and 2.5 per 1000 residents born from 1996 to 2007.